Does financial market stress matter in renewable energy investment? Empirical evidence from BRICS economies - Mohammed Armah; Ebenezer Bugri Anarfo; Emmanuel Numapau Gyamfi; Godfred Amewu (Energy Strategy Reviews, 2025)
Policymakers in BRICS economies face several financial risks in increasing their level of investment in renewable energy. This is because investment in renewable energy is crucial in light of climate change. Although numerous studies have investigated the factors driving renewable energy, little is known about how market stress affects renewable energy. This study explores the critical question that has emerged in the financial literature over the past few decades, namely, the role of financial stress in promoting renewable energy investment. To this end, we employ bivariate and multivariate quantile-on-quantile and wavelet coherence to investigate the effect of financial market stress on renewable energy investment covering the period from 1998 to 2021. Our results show that financial stress adversely affects renewable energy investment during extreme economic downturn. This implies that when market is under stress funding for renewable energy become much harder to secure due to systemic risk. These findings highlight the importance of financial stability for accelerating renewable energy adoption. To sustain renewable growth, BRICS economies need resilient financial policies, such as green financing mechanisms, credit support for renewable firms, and investment-friendly regulations. Ensuring financial stability can help attract long-term capital, making renewable energy a more viable and scalable solution for the future.